Identification, Molecular Cloning, and Functional Characterization of a Wheat UDP-Glucosyltransferase Involved in Resistance to Fusarium Head Blight and to Mycotoxin Accumulation - Gatti, Miriam; Choulet, Frédéric; Macadré, Catherine; Guérard, Florence; Seng, Jean-Marc; Langin, Thierry; Dufresne, Marie (Frontiers in Plant Science, 2018)
Plant uridine diphosphate (UDP)-glucosyltransferases (UGT) catalyze the glucosylation of xenobiotic, endogenous substrates and phytotoxic agents produced by pathogens such as mycotoxins. The Bradi5g03300 UGT-encoding gene from the model plant Brachypodium distachyon was previously shown to confer tolerance to the mycotoxin deoxynivalenol (DON) through glucosylation into DON 3-O-glucose (D3G). This gene was shown to be involved in early establishment of quantitative resistance to Fusarium Head Blight, a major disease of small-grain cereals. In the present work, using a translational biology approach, we identified and characterized a wheat candidate gene, Traes_2BS_14CA35D5D, orthologous to Bradi5g03300 on the short arm of chromosome 2B of bread wheat (Triticum aestivum L.). We showed that this UGT-encoding gene was highly inducible upon infection by a DON-producing Fusarium graminearum strain while not induced upon infection by a strain unable to produce DON. Transformation of this wheat UGT-encoding gene into B. distachyon revealed its ability to confer FHB resistance and root tolerance to DON as well as to potentially conjugate DON into D3G in planta and its impact on total DON reduction. In conclusion, we provide a UGT-encoding candidate gene to include in selection process for FHB resistance.